2004
DOI: 10.5688/aj680490
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Weighting Teaching and Scholarship Activities Among Faculty Members

Abstract: Objective. To identify and weight sets of activities performed by faculty members in the areas of teaching and scholarship. Methods. A panel of faculty members diverse in rank, gender, and discipline convened in a focused discussion and a modified Delphi procedure to identify 29 activities in teaching and 44 activities in scholarship for weighting by the general faculty. Twenty-three of 33 faculty members responded to an anonymous questionnaire eliciting values for each of the activities in a process designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…While several methods exist for documenting and evaluating teaching and scholarship activities, there is a paucity of data regarding procedures and metrics to evaluate faculty practice-related activities. [4][5][6][7][8][9] Guidance regarding competencies and the evaluation of clinical pharmacists are available; however, these documents do not appear to have been widely adopted by academic institutions and only address some potential metrics that could be employed in evaluating faculty practice activities. [14][15][16] Furthermore, in the absence of clear guidance regarding what data should be collected and how it will used, faculty members and administrators have little reason to develop methods, tools, and resources for collecting practice-related data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several methods exist for documenting and evaluating teaching and scholarship activities, there is a paucity of data regarding procedures and metrics to evaluate faculty practice-related activities. [4][5][6][7][8][9] Guidance regarding competencies and the evaluation of clinical pharmacists are available; however, these documents do not appear to have been widely adopted by academic institutions and only address some potential metrics that could be employed in evaluating faculty practice activities. [14][15][16] Furthermore, in the absence of clear guidance regarding what data should be collected and how it will used, faculty members and administrators have little reason to develop methods, tools, and resources for collecting practice-related data.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Increased attention has been paid to the quality and impact of these works in recent years. However, there is a paucity of data regarding the procedures and metrics used to evaluate faculty practice-related activities.…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted at a single institution, faculty members indicated that they placed a greater value on winning an award for research than teaching. 12 Establishment of criteria for best practices with regard to selection of teaching award recipients would help to standardize these awards across colleges and schools of pharmacy and might lead to a higher level of satisfaction among junior faculty members. Draugalis reported a series of best practices in place for teaching awards at colleges and schools of pharmacy, including detailed information on application forms (eg, award criteria, eligibility, selection process), establishment of a selection committee with diverse membership, and awards for teaching in a variety of settings.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the premise that peers should also be involved in the appraisal process, teachers' pedagogical practices have been positively influenced by the development of more complete evaluation systems. These (new) systems are beneficial because they allow for the enhancement of skills, which in turn leads to permanent updates and adaptation to a changing environment (cf Ramos and Moraes, 2000;Desselle et al, 2004;Politis and Siskos, 2004). In spite of the progress achieved in this area, there still is, however, considerable scope for further improvement.…”
Section: Background On Pedagogical Performance Evaluationmentioning
confidence: 97%
“…Despite the progress achieved over the last few decades in the evaluation process of teachers (eg Sparks and Loucks-Horsley, 1989;Wolansky, 2001;Desselle et al, 2004;Avalos and Assael, 2006;Murias et al, 2008;Uzoka, 2008;Ramli et al, 2010;Stoklasa et al, 2011), several authors consider that teaching practices cannot be fully measured given the subjective nature of the appraisal and lack of available indicators. In this sense, Bana e Costa and Oliveira (2012, p 425) defend that '[…] there has been little research on how to integrate objective and subjective approaches adequately […] "most of the evaluation methodologies used […] suffer major flaws in both substance and process" […]' (see also Keeney et al, 2006;Elmore, 2008).…”
Section: Background On Pedagogical Performance Evaluationmentioning
confidence: 97%